(untitled) (Journal of Partial Differential Equations, 2003)
" We discuss a sequence solutions u_03b5 for the E-L equations of the penalized energy defined by Chen-Struwe. We show that the blow-up set of u_03b5 is a H^m-2 - rectifiable set and its weak limit satisfies a blow-up formula. Consequently, the weak limit will be a stationary harmonic map if and only if the blow-up set is stationary."